Low-temperature anomalies of the hardened tin conductivity - Voyevodin, V.N.; Sokolenko, V.I.; Frolov, V.A. (Functional Materials, 2015)
The low-temperature anomalies of conductivity of tin's filaments obtained by cooling of the melt from T ~ (800-900) K with velocity v ~ 10² K/sec are investigated. The samples showed signs of hardening demonstrate the electro-physical and structure abnormalities at the helium temperatures in comparison with superconducting β-Sn modification. Arguments are presented that the semiconducting phases are supercooled allotropic modifications γ- and x-Sn which exist in equilibrium states above T ~ 430 K.